An NHC‐Mediated Metal‐Free Approach towards an NHC‐Coordinated Endocyclic Disilene. Issue 3 (9th February 2022) - Lainer, Thomas; Dange, Deepak; Pillinger, Michael; Fischer, Roland C.; Kelterer, Anne‐Marie; Jones, Cameron; Haas, Michael
Abstract: A convenient metal‐free approach towards an N‐heterocyclic carbene (NHC)‐coordinated disilene 2 is described. Compound 2, featuring the disilene incorporated in cyclopolysilane framework, was obtained in good yield and characterized using NMR spectroscopy and X‐ray crystallography. Density functional theory (DFT) calculations of the reaction mechanism provide a rationale for the observed reactivity and give detailed information on the bonding situation of the base‐stabilized disilene. Compound 2 undergoes thermal or light‐ induced (λ=456 nm) NHC loss, and a dimerization process to give a corresponding dimer with a Si10 skeleton. In order to shed light on the dimerization mechanism, DFT calculations were performed. Moreover, the reactivity of 2 was examined with selected examples of transition metal carbonyl compounds. Abstract : A metal‐free approach towards an endocyclic disilene 2 is reported. The mechanism towards 2 was studied using DFT calculations. Based on quantum chemical calculations, the bonding situation within the endocyclic disilene was determined. Moreover, compound 2 undergoes a thermal or light‐induced dimerization with NHC loss to the corresponding dimer. Selected transition metal carbonyl compounds of 2 have been be prepared.